Economics, Ethics, and Environmental Policy : Contested Choices. - Bromley, Daniel W. (John Wiley & Sons, 2008)
Economics, Ethics, and Environmental Policy: Contested Choices offers a comprehensive analysis of the ethical problems associated with basing environmental policy on economic analysis, and ways to overcome these problems.